The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4322/pmd.2013.019
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of sustainability evaluation in project management

Abstract: Despite the increasing diffusion of project management, it is still incipient the discussion of issues related to sustainability in environmental, social and economic dimensions. This study aims to assess the integration of sustainability into project management. Was used as methodological approach an exploratory research through ex-post fact study conducted in two projects in the food service companies. Data were gathered through project documents and semi-structured interview with projects'stakeholders. As r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…While there are plenty of sources on project management (project portfolio management) or sustainability itself, there are relatively few authors that have linked sustainability with project management [7,10]. This connection involves many concepts depending on the approach adopted by the research team [10].…”
Section: Sustainability In Project Portfolio Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are plenty of sources on project management (project portfolio management) or sustainability itself, there are relatively few authors that have linked sustainability with project management [7,10]. This connection involves many concepts depending on the approach adopted by the research team [10].…”
Section: Sustainability In Project Portfolio Managementmentioning
confidence: 99%
“…The consideration of sustainability is gaining a greater prominence in the field of project portfolio management. There is an increasing understanding of the need to develop methods, tools and techniques to integrate sustainability criteria into the management of projects, as well as a growing need of knowledge and concepts on how to adopt sustainability in project portfolio management [4][5][6][7][8][9][10]. Silvius and Tharp [11] concluded that "the relationship between sustainability and project management is [.…”
Section: Introductionmentioning
confidence: 99%
“…Silvius (2014) reported 250 publications and studies on this topic (compared to 85 publications in 2012 (Silvius et al, 2012, p. 1). However, this research field is relatively new and unexplored (Martens and Carvalho, 2013, p. 111, Brook and Pagnanelli, 2014, p. 59, Daneshpour, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Today there is an increasing understanding of the need to develop methods, tools and techniques to integrate sustainability criteria into the management of projects, as well as a growing need of knowledge and concepts how to adopt sustainability in project management (Ebbesen and Hope, 2013, p. 1, Brook and Pagnanelli, 2014, p. 61, Fernández-Sánchez and Rodríguez-López, 2010, p. 1194, Martens and Carvalho, 2013, p. 112, Tufinio et al, 2013, p. 91, Silvius and Schipper, 2014.…”
mentioning
confidence: 99%
“…And project management could make a valuable contribution in this context [3,4]. Today it is increasingly well understood that methods, tools and techniques need to be developed to integrate sustainability criteria into the management of projects [5,6]; moreover, there is a growing need of knowledge and concepts how to incorporate sustainability into the project management process [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%